2020
DOI: 10.1002/anie.201915155
|View full text |Cite
|
Sign up to set email alerts
|

Oxalyl‐CoA Decarboxylase Enables Nucleophilic One‐Carbon Extension of Aldehydes to Chiral α‐Hydroxy Acids

Abstract: The synthesis of complex molecules from simple, renewable carbon units is the goal of a sustainable economy. Here we explored the biocatalytic potential of the thiamine‐diphosphate‐dependent (ThDP) oxalyl‐CoA decarboxylase (OXC)/2‐hydroxyacyl‐CoA lyase (HACL) superfamily that naturally catalyzes the shortening of acyl‐CoA thioester substrates through the release of the C1‐unit formyl‐CoA. We show that the OXC/HACL superfamily contains promiscuous members that can be reversed to perform nucleophilic C1‐extensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 35 publications
1
32
0
Order By: Relevance
“…Considering the abundance of the enzyme in 2-HIBA-grown cells (Table 1), a specific activity of about 250 nmol min −1 mg −1 (corresponding to a k cat of 0.26 s −1 ) can be deduced, indicating that enzyme preparation and assay protocols still need to be optimized. In addition, a significant overexpression in E. coli could not be established, likely due to insufficient soluble expression as previously observed for human HACL1 and other 2-hydroxyacyl-CoA lyases from prokaryotic origin (Chou et al, 2019;Burgener et al, 2020). In order to purify the enzyme from strain DSM 45062 for kinetic and structural characterization, production of the recombinant protein has to be improved, for example, by employing an actinobacterial expression system such as M. smegmatis (Bashiri and Baker, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the abundance of the enzyme in 2-HIBA-grown cells (Table 1), a specific activity of about 250 nmol min −1 mg −1 (corresponding to a k cat of 0.26 s −1 ) can be deduced, indicating that enzyme preparation and assay protocols still need to be optimized. In addition, a significant overexpression in E. coli could not be established, likely due to insufficient soluble expression as previously observed for human HACL1 and other 2-hydroxyacyl-CoA lyases from prokaryotic origin (Chou et al, 2019;Burgener et al, 2020). In order to purify the enzyme from strain DSM 45062 for kinetic and structural characterization, production of the recombinant protein has to be improved, for example, by employing an actinobacterial expression system such as M. smegmatis (Bashiri and Baker, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The human peroxisomal 2hydroxyphytanoyl-CoA lyase HACL1 (NP_036392.2), for example, catalyzes the decomposition of 2-hydroxyphytanoyl-CoA (2-hydroxy-3,7,11,15-tetramethylhexadecanoyl-CoA) to the aldehyde pristanal (2,6,10,14-tetramethylpentadecanal) and formyl-CoA (Foulon et al, 1999(Foulon et al, , 2005. In addition, it has recently been demonstrated that HACL1 and related prokaryotic TPP-dependent enzymes can even catalyze the reversible acyloin condensation of formyl-CoA with shortand medium-chain carbonyl compounds (Chou et al, 2019;Burgener et al, 2020). Although these 2-hydroxyacyl-CoA lyases and the putative lyase from DSM 45062 are only distantly related (<30% sequence identity at about 90% query coverage), this provisional, only sequence-based functional assignment of WP_018331913.1 let us speculate about a mutase-independent pathway for the degradation of MPD and 2-HIBA proceeding via the decomposition of 2-hydroxyisobutyryl-CoA to acetone and formyl-CoA ( Figure 1A).…”
Section: Organization Of the Lyase-hcl Gene Cluster In A Chiangmaienmentioning
confidence: 99%
“…Moreover, strategies for enzymatic production of high added value alcohols from aminoacids have also been developed [54,55].…”
Section: Cascade Enzymes In Aminoacid Chemistrymentioning
confidence: 99%
“…The methylated R-α-ketoacid obtained recovers its amino group from pyridoxamine (PMP) contained in the enzymes L-TA (IIvE) or D-TA to form L-β-Me-α-amino acids or D-β-Me-α-amino acids, respectively. The third enzyme in the cascade is a halide methyltransferase from Burkholderia xenovorans (HMT), used for SAM regeneration by stereoselective S-methylation of S-adenosylhomocysteine (SAH), through the use of methyl iodide as a methyl donor (Figure8).Moreover, strategies for enzymatic production of high added value alcohols from aminoacids have also been developed[54,55].…”
mentioning
confidence: 99%
“…For example, the formolase enzyme can convert formaldehyde into dihydroxyacetone (8) or glycolaldehyde (13), which can be assimilated by either natural or engineered enzymes (14). An engineered enzyme can convert formyl-CoA and formaldehyde into glycolyl-CoA and then glycolate, which can be assimilated naturally (15,16). The common advance needed to enable all of these pathways is the reduction of formate to formaldehyde.…”
Section: Introductionmentioning
confidence: 99%